Reconfiguration of the Authority of State Prosecutors After the Reform of the Prosecutor's Office: Legal Certainty and Public Authority Governance in Indonesia - Michele Moreno; Fauzie Yusuf Hasibuan; Maryano Maryano (Advances In Social Humanities Research, 2026)
This research examines the post-amendment reformulation of the authority of Indonesia’s State Attorneys within the Prosecutor’s Office and its implications for legal certainty. Using a doctrinal research design, the study analyzes amended statutory provisions, implementing regulations, judicial decisions, and selected comparative materials, combined with an informed literature screening process. The findings demonstrate a paradigmatic shift from a narrowly reactive litigation role toward a preventive and strategic model encompassing legal opinions, policy assistance, and project accompaniment. Nevertheless, the reform simultaneously introduces normatively open-textured clauses and limited procedural guidance, generating risks of overlapping competences, uneven administrative practice, and fragmented judicial interpretation. When assessed against theories of public authority, the rule of law, and good governance, the reform appears only partially aligned with the requirements of predictability, coherence, and accountability. The article contributes conceptually by proposing a legal-certainty-oriented framework for evaluating prosecutorial empowerment in administrative governance, and practically by identifying the need for harmonized secondary regulations, standardized coordination mechanisms, and strengthened external oversight. Overall, the study argues that institutional strengthening through legislative amendment must be accompanied by precise normative architecture to ensure that expanded prosecutorial functions reinforce, rather than undermine, the stability and credibility of the legal system and democratic public administration outcomes that are increasingly necessary in today’s world.